Performance Analysis Techniques for Multi-Soft-Core and Many-Soft-Core Systems. (26th July 2012) - Castells-Rufas, David; Fernandez-Alonso, Eduard; Carrabina, Jordi
Abstract : Multi-soft-core systems are a viable and interesting solution for embedded systems that need a particular tradeoff between performance, flexibility and development speed. As the growing capacity allows it, many-soft-cores are also expected to have relevance to future embedded systems. As a consequence, parallel programming methods and tools will be necessarily embraced as a part of the full system development process. Performance analysis is an important part of the development process for parallel applications. It is usually mandatory when you want to get a desired performance or to verify that the system is meeting some real-time constraints. One of the usual techniques used by the HPC community is the postmortem analysis of application traces. However, this is not easily transported to the embedded systems based on FPGA due to the resource limitations of the platforms. We propose several techniques and some hardware architectural support to be able to generate traces on multiprocessor systems based on FPGAs and use them to optimize the performance of the running applications.